2017
DOI: 10.1002/pc.24676
|View full text |Cite
|
Sign up to set email alerts
|

Development of cellulose nanocrystal‐reinforced polylactide: A comparative study on different preparation methods

Abstract: A masterbatch of polylactide (PLA) containing cellulose nanocrystals (CNCs) prepared via a solution-cast method was further diluted with neat PLA in the melt state using either a twin-screw extruder or an internal batch mixer to reach a final CNC content of 4 wt%. For the sake of comparison, a direct melt mixing method was employed to prepare PLA-CNC composites. Then, the efficiency of the preparation methods was assessed by comparing the morphological, rheological and thermomechanical properties of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…In other words, as there was no CNC surface treatment or compatibilizer, the dispersed CNC nanoparticles dramatically tended to reagglomerate during the melt process. [ 31 ] Although this may not be favorable but still the viscoelastic properties showed enhancements when compared to those samples that directly melt mixed (the results are not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, as there was no CNC surface treatment or compatibilizer, the dispersed CNC nanoparticles dramatically tended to reagglomerate during the melt process. [ 31 ] Although this may not be favorable but still the viscoelastic properties showed enhancements when compared to those samples that directly melt mixed (the results are not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the hydrophilic structure of CNC, which causes the formation of CNC agglomerates in the matrix. [ 25,31 ] Besides the high surface energy of CNC, the presence of strong hydrogen bonding among these nanoparticles prevents their dispersion in PLA. Various studies have been reported on improving of CNC dispersion in PLA matrix by using surface‐modified CNCs, [ 32,33 ] compatibilizer, [ 34,35 ] or different CNC preparation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has attracted a great deal of scientific consideration for high‐performance applications . Therefore, CNCs can be used in many applications such as reinforcing agents in polymer nanocomposites due to their incredible properties …”
Section: Introductionmentioning
confidence: 99%
“…Solvent casting of PLA/CNC nanocomposites results in the development of a strong CNC percolation network without the problem of thermal degradation of PLA, a problem associated with melt mixing. [172] Bagheriasl et al [191,192] achieved superior dispersion of CNC nanoparticles in PLA/CNC nanocomposites produced by solvent casting with DMF. They also observed that compared melt mixing in TSE, solvent casting led to a better dispersion of nanoparticles in PLA nanocomposites containing 4 wt% CNC.…”
Section: Cnc-containing Pla Nanocompositesmentioning
confidence: 99%